Increased expression of AQP 1 and AQP 5 in rat lungs ventilated with low tidal volume is time dependent. - Gustavo Fabregat; José García-de-la-Asunción; Benjamín Sarriá; Julio Cortijo; José De Andrés; Manuel Mata; Ernesto Pastor; Francisco Javier Belda (PLoS ONE)
Background and goals Mechanical ventilation (MV) can induce or worsen pulmonary oedema. Aquaporins (AQPs) facilitate the selective and rapid bi-directional movement of water. Their role in the development and resolution of pulmonary oedema is controversial. Our objectives are to determine if prolonged MV causes lung oedema and changes in the expression of AQP 1 and AQP 5 in rats. Methods 25 male Wistar rats were subjected to MV with a tidal volume of 10 ml/kg, during 2 hours (n = 12) and 4 hours (n = 13). Degree of oedema was compared with a group of non-ventilated rats (n = 5). The expression of AQP 1 and AQP 5 were determined by western immunoblotting, measuring the amount of mRNA (previously amplified by RT-PCR) and immunohistochemical staining of AQPs 1 and 5 in lung samples from all groups. Results Lung oedema and alveolar-capillary membrane permeability did not change during MV. AQP-5 steady state levels in the western blot were increased (p<0.01) at 2 h and 4 h of MV. But in AQP-1 expression these differences were not found. However, the amount of mRNA for AQP-1 was increased at 2 h and 4 h of MV; and for AQP 5 at 4 h of MV. These findings were corroborated by representative immunohistochemical lung samples. Conclusion In lungs from rats ventilated with a low tidal volume the expression of AQP 5 increases gradually with MV duration, but does not cause pulmonary oedema or changes in lung permeability. AQPs may have a protective effect against the oedema induced by MV.